Determinants of Academic Mentoring in Higher Education: Evidence from a Research University, Educational Process - Abugre, J.B.; Kpinpuo, S.D. (My University, 2017)
Research has shown that most young and inexperienced faculty members require assistance in developing their career and meeting their teaching quota through mentoring. However, academic mentoring has not been effective in many research universities, especially those in the developing world. This study has investigated the factors that facilitate academic mentoring in a typical research university. The study adapted a quantitative methodology by drawing from a sample of 244 senior and junior teaching staff of a public research university in Ghana and used Multiple Regression as the basis for the study analysis to test the hypotheses. Findings showed a strong positive relationship between institutional career support and the process of mentoring. Findings also showed a strong positive mentoring relationship between senior faculty and inexperienced faculty, as well as between colleague faculty. Similarly, findings showed a very low presence of academic mentoring in the University of Ghana. This work contributes strongly to academic mentoring and discovers some legitimate antecedents of mentoring in institutions of Higher Education. By this, the work provides HE institutions with the value of developing their internal human capital asset that can leverage their performance.
Keywords: mentoring; determinants of mentoring; institutional career support; co-worker support; higher education; human resource capabilities